Weighted parsimony phylogeny of the family Characidae (Teleostei: Characiformes) - Mirande, Juan Marcos (2009)
The family Characidae, including more than 1000 species, lacks a phylogenetic diagnosis, with many of its genera currently considered as incertae sedis. The aims of the present study are to propose a phylogenetic diagnosis and to assess higher-level relationships of and within Characidae. In this regard, 360 morphological characters are studied for 160 species of Characidae and related families. Phylogenetic analyses under implied weighting and self-weighted optimization are presented, exploring a broad range of parameters. The analysis under self-weighted optimization is innovative for this size of matrices. Familial status of Serrasalmidae is supported, and Acestrorhynchidae and Cynodontidae are included in a monophyletic Characidae. Engraulisoma taeniatum is transferred from Characidae to Gasteropelecidae. Thus constituted, the monophyly of Characidae is supported by seven synapomorphies. A new subfamily, Heterocharacinae, is proposed, and the subfamilies Aphyocharacinae, Aphyoditeinae, Characinae, Gymnocharacinae, and Stevardiinae are redefined. The Glandulocaudinae are included in Stevardiinae together with remaining members of ‘‘clade A’’ (sensu Malabarba and Weitzman, 2003. Comun. Mus. Ciênc. Tecnol. PUCRS, Sér. Zool. 16, 67–151.) and the genera Aulixidens and Nantis. Most incertae sedis genera are assigned, at least tentatively, to a phylogenetically diagnosed clade.